Multi-target Approaches of Epigallocatechin-3-O-gallate (EGCG) and its Derivatives against Influenza Viruses - da Silva-Júnior, Edeildo F.; Silva, Leandro Rocha (Current Topics in Medicinal Chemistry, 2022)
Influenza viruses (INFV), the Orthomyxoviridae family, are mainly transmitted among humans via aerosols or droplets from the respiratory secretions. However, fomites could be a potential transmission pathway. Annually, seasonal INFV infections account for 290-650 thousand deaths worldwide. Currently, there are two classes of approved drugs to treat INFV infections, being neuraminidase (NA) inhibitors and blockers of matrix-2 (M2) ion channel. However, cases of resistance have been observed for both chemical classes, reducing the efficacy of treatment. The emergence of influenza outbreaks and pandemics calls for new antiviral molecules that are more effective, and that could overcome the current resistance to anti-influenza drugs. In this context, polyphenolic compounds are found in various plants, and these have displayed different multi-target approaches against diverse pathogens. Among these, green tea (Camellia sinensis) catechins, in special epigallocatechin-3-O-gallate (EGCG), have demonstrated significant activities against the two most relevant human INFV, subtypes A and lineages B. In this sense, EGCG has been found to be a promising multi-target agent against INFV since it can act inhibiting NA, hemagglutination (HA), RNA-dependent RNA polymerase (RdRp), and viral entry/adsorption. In general, the lack of knowledge about potential multi-target natural products prevents an adequate exploration of them, increasing the time for developing multi-target drugs. Then, this review aimed to compile most relevant studies showing the anti-INFV effects of EGCG and its derivatives, which could become antiviral drug prototypes in the future.
Keywords: Antiviral